GARRISON RECRUITMENT OF THE FORTRESS OF THE HOLY CROSS (1722-1735): ON THE MATERIALS OF THE CENTRAL STATE ARCHIVE OF THE REPUBLIC OF DAGESTAN - Abdusalamov, Magomed-Pasa Balasovic; Cekulaev, Nikolaj Dmitrievic (History, Archeology and Ethnography of the Caucasus, 2020)
Basing on the materials of the Central State Archive of the Republic of Dagestan, the paper attempts to reconstruct the history of the stay of the Russian imperial troops in Dagestan in the first third of the 18th century. From the objective stance, considering achievements of the national caucasiology, on the basis of in-depth study, analysis and synthesis of archive materials, the authors aim to determine the role of the garrison of the fortress of the Holy Cross in implementation by the Russian Empire of the Caucasian policies in Dagestan. The paper considers the system of the garrison recruitment, reveals all aspects of activity of these troops, starting from organization to garrison service. Stored in the Central State Archive of the Republic of Dagestan, the fund №382 “Commandant of the fortress of the Holy Cross”, as well as documents for the period of 1722-1735 from the fund №18 and 335 are the main sources for history of both the fortress and its recruitment. They contain military records, which present the everyday activities of the garrison troops of the Lower Corps of the Russian Empire. The methodological and theoretical basis of the article is comprised of the main principles of historical science: objectivity, scientific nature and historicism, intended to study historical events and facts in specific historical conditions, their consideration in a comparative historical plan. The authors analyze the procedure of enlisting and sending recruits to the fortress of the Holy Cross; specify the fact that the procedure was regulated by the government orders. It is revealed that the recruitment of the garrison of the Holy Cross was carried out at the expense of the recruiters, coming primarily from the cities of the Volga region. The study also points out the fact that the officer corps of the garrison regiments of the fortress of the Holy Cross was staffed at the expense of the estate of the nobles of the Russian Empire on the basis of the principle of electivity from among the non-commissioned officers, chief officers.